Phonological coherence in the view of linguists - Hayat Ali Hussein, Asst. Dr. (lark, 2025)
Modern morphological studies have focused on word structure, which consists of syllables, forms, and phonetic elements that convey a specific and definite meaning. These two disciplines were closely linked in the first linguistic lesson. Morphology has received significant attention in linguistic studies, both ancient and modern. Morphology is considered one of the most important and noble sciences, due to its significant importance and profound influence on word structure in verbal discourse. Therefore, this science has received the attention of scholars, especially ancient scholars. The writings of our early scholars included mixed topics between phonetics and morphology. These topics were then separated until they became independent books, some of which were specific to morphology and others specialized in phonetics. This is because linguists have seen a close and interconnected relationship between these two disciplines in any linguistic study. Morphology is the inversion of the facets of a word, and this inversion, in turn, results in phonetic transformations such as vowelization, assimilation, and other phonetic phenomena. Therefore, we can consider morphology the science closest to phonology. Many morphological studies are based on phonetics, and are therefore considered "phonetic morphological studies." This interconnectedness and harmony are clear to anyone who carefully examines Arabic linguistic studies. Early scholars attempted to identify the changes that occur in the structures of the Arabic word, which in turn depend on sounds. Therefore, morphological topics cannot be studied unless this study is preceded by a thorough understanding of phonetics. From this understanding, we can realize that many morphological issues cannot be understood or understood without a study of linguistic sounds, so that such a study can be complete, correct, and meet the requirements of sound linguistic research.